Study of urban atmospheric heat islands and its mitigation in São Bernardo do Campo-SP - Simeão, Adriel de Barros; Scopel, Stefânia Bernardi; Valverde, María Cleofé (Revista Hipótese, 2019)
The objective of this study was to characterize the atmospheric urban heat islands in the city of São Bernardo do Campo-SP, in order to understand their impact on the thermal comfort of the region and to propose mitigating measures of the intensity of the phenomenon. The results indicated an urban heat island of medium magnitude (2.4°C to 2.9°C). Among mitigation technologies, it is recommended the application of TPO (thermoplastic polyolefin) roofs for small sloping roofs and pigmented metallic roofs for sheds and industrial areas, as well as the implantation of more green areas in public, institutional and private spaces.
Keywords: Heat islands; Urbanization; Use and occupation of soil; Mitigation